Deportations in the Nazi Era : sources and research - Deportations in the Nazi Era - Sources and Research; Borggräfe, Henning 1981- HerausgeberIn; Jah, Akim 1967- HerausgeberIn (Arolsen research series, 2023)
During the Nazi era, about three million Jews – half the victims of the Holocaust – were deported from the German Reich, the occupied territories, as well as Nazi-allied countries, and sent to ghettos, camps, and extermination centers. The police and the SS also deported tens of thousands of Sinti and Roma, mainly to the Auschwitz concentration and extermination camp, where most of them were killed. Deportations were central to National Socialist persecution and extermination. In November 2020, an international conference organized by the Arolsen Archives focused on the various historical sources, their research potential, and (digital) methods of cataloging them. It also explored new (systematizing and comparative) approaches in historical research. This volume features over 20 contributions by scholars from different countries and with a variety of perspectives and questions. The main geographical focus is on deportations from the German Reich and German-occupied Southeastern Europe